2003
DOI: 10.1002/chin.200334036
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Epoxidation of Olefins with ≥ 99% Selectivity and Use of Hydrogen Peroxide.

Abstract: EpoxidationEpoxidation O 0218 Efficient Epoxidation of Olefins with ≥ 99% Selectivity and Use of Hydrogen Peroxide. -A green route for the efficient and selective epoxidation of a wide variety of olefins using H2O2 as oxidant and a lacunary Keggin-type silicodecatungstate as catalyst is developed. The catalytic epoxidation proceeds with ≥99% selectivity to epoxide, ≥99% efficiency of H2O2 utilization, high stereospecificity and easy recovery of catalyst. -(KAMATA, K.; YONEHARA, K.; SUMIDA, Y.; YAMAGUCHI, K.; H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
103
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(104 citation statements)
references
References 1 publication
1
103
0
Order By: Relevance
“…Polyoxometalates and heteropolyoxometalates (POMs) are widely known as functional materials in catalytic oxidation 25 reactions, [1][2][3][4][5][6][7][8][9][10][11][12][13][14] metallorganic-POM hybrid catalysts. 9 In particular, the facile incorporation of transition-metals into lacunary-type POMs has attracted significant interest for preparation of oxidation catalysts with high activity.…”
Section: Introductionmentioning
confidence: 99%
“…Polyoxometalates and heteropolyoxometalates (POMs) are widely known as functional materials in catalytic oxidation 25 reactions, [1][2][3][4][5][6][7][8][9][10][11][12][13][14] metallorganic-POM hybrid catalysts. 9 In particular, the facile incorporation of transition-metals into lacunary-type POMs has attracted significant interest for preparation of oxidation catalysts with high activity.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Mizuno and co-workers reported the synthesis of (Bu 4 N) 4 [γ-SiW 10 O 34 (H 2 O) 2 ] (4, Figure 3), which displays remarkable regioselectivity in olefin epoxidation and quantitative utility of hydrogen peroxide. 18,19 The latter feature of 4 prompted us to consider its utility in the oxygenation of sulfides by H without and with imidazole resulted in the complete consumption of CEPS in 6 h (entry 1) and 2 h (entry 2), respectively, while sulfones were not detected among the products. Prevention of sulfone formation is significant in the decontamination of mustard gas since its sulfone is also highly toxic.…”
Section: Report Documentation Page (Sf298) (Continuation Sheet)mentioning
confidence: 99%
“…It is also found that the mononuclear Mn-TACN system can activate t BuO 2 H and exhibits one of the highest TOFs (turn-over frequency) in the oxygenation of sulfides by t BuO 2 H. Also identified is an organic soluble polyoxometallate catalyst, (Bu 4 N) 4 [γ-SiW 10 6 These catalysts possess some of most desired features for a green Decon system: low cost, ease of transport and aqueous-based chemistry, and their catalytic chemistry are still subject to intense study in our laboratory. Originated from early interests in phosphate esters and TACN compounds, we also published on the research of TACN-Cu complexes, [18]ane-N 6 Cu compounds and their phosphate monoester binding events. [7][8][9] More recently, our laboratory made two discoveries that bear great significances with Decon chemistry.…”
mentioning
confidence: 99%
“…In contrast to such classical "nongreen" processes, H2O2-based catalytic epoxidation has some advantages because it makes environmentally benign H2O as a sole by-product and because it is rather inexpensive compared with organic peroxides and peracids [11]. Transition metal compounds such as metalloporphyrin [12], titanosilicates [13], methyltrioxorhenium [14], tungsten compounds [15][16][17][18], polyoxometalates [19,20], and manganese complexes [21] have been employed as a catalyst for H2O2-based epoxidation, either homogeneous or heterogeneous.…”
Section: Introductionmentioning
confidence: 99%